Les vicissituds de la traducció al castellà d'elements heroics i medievals del Canigó, de Jacint Verdaguer. El cas de «La Maladeta». - VILARDELL, LAURA (Scripta, 2014)
In this article we study the translation's difficulties of «La Maladeta», an extract of Canigó by Jacint Verdaguer. We think that this piece is enough representative of the Verdaguer's epic poem theme, because it has been one of the most translated sections of the poem, and, in addition, it contents heroic and medieval elements. So, we have considered appropriate to make the analysis of each translation of this passage, in order to draw some conclusions which help us to assess the quality of each version.